Clinico-demographic Profile and Outcome of COVID-19 Patients Admitted in the ICU of Enam Medical College Hospital - Begum, Nasima; Rahman, Nelufa Tahera; Khanum, Easnem; Islam, Md Ashraful; Haque, Md Rezaul (Journal of Enam Medical College, 2024)
Background: COVID-19 is an acute respiratory disease caused by a novel coronavirus (SARS-CoV-2) which first emerged in China in December 2019. Then it rapidly spread globally including Bangladesh with devastating damage to the public health. The aim of the study was to describe the demographic characteristics, clinical features and outcome of COVID-19 patients admitted into the ICU of Enam Medical College Hospital (EMCH) from 1 February 2021 to 30 April 2021. Materials and Methods: It was a prospective observational study with a convenient sampling technique. Separate preset questionnaire was used to collect the data. RT-PCR for Covid-19 positive cases were included and the patients who did not complete the treatment were excluded from the study. Data regarding demographic, clinical and laboratory parameters, management and outcome of 105 COVID-19 patients were collected and analyzed. Results: Total 136 patients were admitted during the study period. Among them 105 patients were RT-PCR positive. The mean age of the patients was 55.12±12.7 years with 60.9% male and 39.0 % female. Majority of them (70.4%) came from urban areas and 46.6% were from upper socio-economic clas; 57.1% were smokers and 42.8% were non-smokers. Fever (95.2%), cough (90.47%), anosmia (61.9%), dyspnea (58.0%), fatigue (40%) and diarrhea (23.8%) were the predominant symptoms. Common comorbidities were diabetes mellitus (89, 84.7%), cardiac disease (88, 83.8%), hypertension (85, 80.9%), chronic obstructive pulmonary disease (72, 68.5%), and renal disease (18, 17.1%). Oxygen was delivered through high flow nasal cannula (38%), non-invasive ventilation (33%) and mechanical ventilation (40.9%). Only 16.1% received two doses of COVID-19 vaccine. Majority of the patients (56.1%) stayed for 1−7 days with a mean duration of ICU stay 9.09±5.9 days. Total 61 patients (58.09%) died due to COVID-pneumonia with a mortality rate 58.09%. Conclusion: In spite of appropriate care and ICU support, the mortality of COVID-19 was high. So, in order to prevent the disaster of the disease mass education about basic sanitation, personal hygiene, social distancing and mass vaccination should be ensured. Special attention should be provided to aged patients with comorbidities. J Enam Med Col 2022; 12(1): 43−49